Investigation of the Granulometric and Mechanical Properties of Inorganic Used Sand - Dargai, Viktória; Varga, László (International Journal of Engineering and Management Sciences, 2020)
This paper examines the use of a modified inorganic binder in metal-alloy casting. The results of investigations regarding the effect of reusing the used sand multiple times without reclamation. The technological properties of silica sand with inorganic binders were presented, two different temperatures were applied to make the used sands. After lump crushing the inorganic used sand was recycled in order to make a new sand mixture. Our work was focused on the effect of multiple usage of inorganic used sands on the mechanical and granulometric properties prepared with modified inorganic binder.